The potential of novel African isolates of Phthorimaea operculella granulovirus for the control of Tuta absoluta - Ben Tiba, S.; Larem, A.; Laarif, A.; Fritsch, E.; Undorf-Spahn, K.; Ekesi, S.; Wennmann, J.T.; Kroschel, Jürgen; Fattouch, S.; Jehle, J.A.; Mohamed, S.A. (Wiley, 2019)
Phthorimaea operculella granulovirus (PhopGV) is infectious for larvae of different Gelechiidae insect species, including Tuta absoluta and Phthorimaea operculella. As these are major economic pests in North and sub‐Saharan Africa as well as in the Mediterranean area, the development of locally suitable biocontrol agents is essential. We have studied five isolates of PhopGV from Tunisia (Tns16, Tu1.11 and Tu2.11), Kenya (Ken13) and Yemen (Ym14) for their biological activity and the sequence polymorphism of their granulin and ecdysteroid UDP‐glucosyltransferase (egt) genes and allocated the isolates to two different egt types. Infection experiments with neonate larvae of T. absoluta and P. operculella demonstrated their pathogenicity to both host species. The isolate PhopGV Tu1.11 was the most virulent one for T. absoluta but had a relatively low infectivity to two P. operculella populations originating from Italy and Tunisia.